Job search and savings - Lentz, Rasmus,Tranæs, Torben (Univ., Center for Economic Studies, 2001)
In this paper we consider a risk averse worker who is moving back and forth between employment and unemployment; layoffs are random and beyond the worker`s influence, while the reemployment chance is directly affected by search effort. We characterize the worker`s optimal savings and jobsearch behavior as well as the resulting consumption paths and wealth formation. In general, all decisions will depend on the current level of wealth.
Literaturverz. S. 29 - 30
Keywords: Arbeitspapier; Graue Literatur; Suchtheorie; Arbeitslosigkeit; Dauer; Vermögenseffekt; Sparen; Konsumtheorie; Intertemporale Entscheidung; Theorie